Características de las cartas al editor publicadas en revistas de educación médica editadas en español, 2015-2020 - Dextre-Vilchez, Sergio Armando (2022)
Introduction: Readers express their comments in the form of letters to the editor about previously published articles, original research that does not reach the original article, or general topics that require attention because of their novelty. It has the possibility of receiving a response in the form of a reply. Objective: Describe the characteristics of the letters to the editor published during the period 2015-2020 in the journals of medical education in Spanish indexed in SciELO or Scopus. Method: A descriptive, retrospective, and bibliometric study of the letters to the editor of the journals: Educación Médica, Educación Médica Superior, Investigación en Educación Médica y la Revista de la Fundación Educación Médica. The period covered was from January 2015 to December 2020. Results: The annual average of letters to the editor was 13.23%, with a minimum value of 6.58% in 2015 and a maximum of 18.41% in 2018. The institutional affiliation of universities was the most frequent (84.71%). The majority of authors had Peruvian affiliation (43.80%) and the male sex (78.93%). The letters written in Spanish were 99.59%. In relation to the general purpose, the general comments (42.56%) and comments on previously published articles (40.50%) predominated. The average number of citations was 4.24, with own findings having the highest average at 6.39. Only 11 letters had replies. The average number of authors was 2.02. Conclusions: The publication of letters to the editor had an increase over the years, its use as a means of criticism is still frequent; however, feedback and exchange of ideas through replication was not frequent.